Nilai-Nilai Pendidikan Agama Hindu dalam Upacara Metatah Terhadap Pembelajaran Panca Yadnya - Wirawan, Ida Bagus Dharma Putra; Marsono, Marsono (Jayapangus Press, 2022)
Yadnya can be understood as selfless sacrifice, sincerity, and a pure heart. The implementation of yadnya based on bhakti is increasingly complex when it is associated with the teachings of Panca Yadnya. Among the five categories of yadnya, manusa yadnya is one form of purification ritual intended for humans from the womb to death. The Hindu tooth cutting or metatah ceremony is one of the human yadnya rituals. This ceremony becomes mandatory before a person enters the representative stage of his life. So that the understanding of the community and students is not only limited to recognizing the name and purpose of the ceremony, but also to absorb and apply the spiritual meaning contained in it. This can be achieved through more intensive efforts in religious education, This research uses a qualitative descriptive method. The results of the research state that the concept of education in the implementation of the metatah ceremony includes: 1). Spiritual education. 2). Cultural education. 3). Ethical values. 4). Social value of teamwork. Thus, Metatah is not only a cultural heritage tradition, but also a real manifestation of the teachings of Panca Yadnya, creating harmony and balance between individuals, God, ancestors, fellow humans, and nature in the context of Hindu life in Bali.